13th International Chemical and Biological Engineering Conference (CHEMPOR 2018): book of short abstracts - Coutinho, João Araújo Pereira (2019)
University of Aveiro and Ordem dos Engenheiros proudly welcome all participants to the 13th International Chemical and Biological Engineering Conference - CHEMPOR 2018. Welcome to Aveiro! During three days, from October 2nd to 4th, more than 370 participants from Industry and Academia gathered at Centro Cultural e de Congressos de Aveiro to discuss recent developments and future directions in different areas of chemical engineering, materials science and engineering, biotechnology and biological engineering. CHEMPOR 2018 aims to be a forum for the debate of societal challenges related to energy, the environment, and the efficient use of natural resources and materials, all of which require innovative solutions complying with sustainability criteria. In 2017 Portuguese exports increased circa 11 % reaching the highest value of the Gross Domestic Product (in a time horizon of 23 years). Portugal’s Ministry of Economy estimates that capital-intensive industries (such as chemicals and polymers producers) and manufacturing industries (including food, textile, paper, cork, wood panels and metal producers) account for over 50 % of the overall value of the exportations. In this context, CHEMPOR 2018 emerges as a privileged forum to discuss technological and scientific issues that will promote economic growth through innovation. The Organizing Committee accepted more than 345 communications, of which 83 oral presentations, after peer reviewing. Internationally recognized scientists were invited to deliver 6 Plenary Lectures and 6 Keynote Speeches. On the opening day of CHEMPOR 2018, the Portuguese Minister of Economy, Professor Manuel Caldeira Cabral, made a communication in the presence of dozens of industrial sponsors. Just before the closing session, the Professor Almiro Castro Award (sponsored by PARALAB) was granted , for the second time, and prizes were awarded to the best Oral and Poster Communications presented during the Conference. The Organizing Committee of CHEMPOR 2018 acknowledges all authors for their contributions, all colleagues involved in the organization of the program, and the generosity of all sponsors. We wish you a memorable Conference both scientifically and socially.